Quality assurance in CT: implementation of the updated national diagnostic reference levels using an automated CT dose monitoring system. Issue 7 (July 2018) - Appel, E.; Kröpil, P.; Bethge, O.T.; Aissa, J.; Thomas, C.; Antoch, G.; Boos, J.
Abstract : Aim: To evaluate the implementation of the updated computed tomography (CT) diagnostic reference levels (DRLs) from the German Federal Office for Radiation Protection into clinical routine using an automatic CT dose monitoring system. Methods and materials: CT radiation exposure was analysed before and after implementing the updated national DRLs into routine clinical work in 2016. After the implementation process, institutional CT protocols were mapped to the anatomical regions for which DRLs were provided. Systematically, protocols that exceeded the thresholds were optimised and analysed in detail. The CT radiation output parameters analysed were volumetric CT dose index (CTDIvol) and dose–length product (DLP). Three radiologists evaluated subjective image quality using a three-point Likert scale. Results: The study included 94, 258 CT series (from 27, 103 CT examinations) in adult patients performed in 2016. When averaged over all body regions with available DRL, institutional CTDIvol/DLP values were always below the DRLs (65.2±32.9%/67.3±41.5% initially; 59.4±32%/60.5±39.9% after optimisation). Values exceeding the national DRLs were found for pelvis ( n =268; CTDIvol 107.7±65.7%/DLP 106.3±79.3%), lumbar spine ( n =91; 160.8±74.7%/175.2±104.1%), and facial bones ( n =527; 108±39%/152.7±75.7%). After optimisation, CTDIvol and DLP were 87.9±73%/87.8±80.8% for the pelvis, 67.8±33.2%/74.5±50.6% for the lumbar spine and 95.1±45.8%/133.3±74.6% for the viscerocranium. Conclusion: An automatic CT dose monitoring system enabled not only comprehensive monitoring of a DRL implementation process but can also help to optimise radiation exposure. Highlights: Automated dose management systems enable a comprehensive analysis of large-scale CT dose data. Automated dose management systems can be used to analyze the implementation process of diagnostic reference levels. Automated dose management systems can help to identify CT dose outliers.